Case Report: De Garengeot’s hernia. Appendicitis within femoral hernia. Diagnosis and surgical management - Sibona, Agustin (Int J Surg Case Rep, 2016)
INTRODUCTION: Abdominal wall hernias remain as one of the most common problems that the general surgeon has to treat. Although usually straightforward and easy to diagnose by the experienced hands, obstacles appear when contents of the hernia sac include organs. The presence of the appendix inside a femoral hernia (De Garengeot’s hernia) is a rare entity which represents multiple challenges, both diagnostic and therapeutic. CASE PRESENTATION: We present a case of a 36-year-old female patient who originally presented to the ED with abdominal/groin pain and a new onset of right inguinal swelling. DISCUSSION: Contrary to the usual presentation, where an appendix is incidentally found during hernia repair, we were able to make the diagnosis by CT scan before surgery. This placed us on an ideal standpoint to plan the surgical management. We approached our case laparoscopic first, where a distally gangrenous appendix was reduced intraabdominally. As purulent exudates were present on hernial sac, femoral hernia repair was achieved with McVay techniche. CONCLUSION: Although rare, the finding of a strangulated appendix within a femoral hernia represents a challenge. Here we present a case that may guide the surgeon who faces a similar case in the future.